Pedagogical conditions of sprint effectiveness increase - Nazarenko, L. D.; Katenkov, A. N.; Anisimova, E. A. (The Russian Journal of Physical Education and Sport, 2016)
Sprint is one of the most spectacular kinds of athletics, which attracts a lot of audience. A high level of competition among the strongest sprinters, different sport schools, which create effective technologies of the results improvement in competitive activity, demand reliability and stability of sports achievements. However, the difficulty of this problem doesn`t allow to find its well-defined solution and many research works are dedicated to the separate questions of sportsmanship improvement among sprinters. Research methods: scientific-methodical literature analysis and systematization, pedagogical experiment, questionnaire survey, testing, statistical data manipulation. Materials. Sprint technique improvement demands efforts coordination of trainers and sportsmen in order to find new ways of sports training process realization and has a clear oriented individual character, conditioned by a complex of different factors. This article presents the main pedagogical conditions, the realization of which is directed at an individual technique formation of the running steps fulfillment and effectiveness increase of the training process. Results.The results of the pedagogical experiment showed the importance of each revealed pedagogical conditions realization, which present a program of a trainer`s and a sportsman`s actions. According to specially created criteria the formation level of an intellectual, spiritual-moral, psychological-emotional sphere and a sportsman`s volitional potential were estimated. The methodology, based on these pedagogical conditions use, helps to improve physical readiness indices and provides the level of special readiness increase as the base for a rational technique of the running steps mastering. Conclusion. The results of the pedagogical experiment proved the effectiveness and expediency of the created methodology use in the training process of sprinters. Fundamentality of the theoretical theses, provided in the content of pedagogical conditions, underlines the versatility and depth of the approach to the set problem solution, which provides not only physical and technical readiness indices increase, but other sides of sports training, including intellectual, spiritual-moral spheres, personal qualities formation, which condition the set aim realization.